Informação, conhecimento e adesão à vacinação contra o papilomavírus humano oferecida pelo sistema público de saúde às adolescentes e a opinião de seus responsáveis - Vargas, Viviane Ianez [UNIFESP] (2018)
Objective: Asses knowledge about the public campaign of Brazilian vaccination against the human papillomavirus (HPV) in different social classes and detect possible reasons that led the fall in acceptance of the campaign. Methodos: 1405 questionnaires were distributed among girls in age vaccine and its responsible in different institutions in the city of São Paulo. Results: Fathers and daughters of low economic level showed less knowledge about the virus and the vaccine than those of middle and upper class. All walks of life were affected by lack of information and active search of adolescents in schools as done in the first phase of public campaign of vaccination. Conclusion: Inadequate information from media sources about the HPV virus a vaccination adversely affected the percentage of vaccines applied. The lower-income class suffered more damage from misinformation. Parents, in general, even showing acceptability about the vaccine, did not seek to complete the doses of the other stages of vaccination available at public health outposts.